Sinkronisasi Materi Muatan Perda Berbasis Syariah - Hayatun Na’imah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
The regional regulation (Perda) as one of the legal products prevails in the Republic of Indonesia (RI) has its place in the hierarchical structure of the Indonesian legislation. The emergence of Shari'a-based local regulations in various regions in Indonesia is related to the emergence of regional autonomy. Shari'a based regional regulations cannot be directly said to be good or not according to the law, nor can it be said to be in line with or contrary to the existing legislation. There are several parameters to assess the regional regulations, namely by the Executive Review conducted by the Ministry of Home Affairs, the Judicial Review carried out by the Supreme Court and the Legislative Review by the Legislature. Through these parameters it can be seen whether Sharia-based regional regulation (Perda) are referred to as part of the existing legislation in Indonesia.